The Influence of Sustainability Reporting and Risk Management on the Profitability of Publicly Listed Banks - Janice, Laurensia; Handoko, Jesica (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study examines the influence of sustainability reporting and risk management on the profitability of Indonesian publicly listed banks on the Indonesia Stock Exchange (IDX) during 2019 to 2023. The study evaluates the causal relationship between dependent variable, which is the profitability (measured by ROA and ROE) and independent variables, including sustainability reporting disclosure and CAR, NPL, and LDR. This study also uses control variables, such as leverage (DER), bank size, and COVID-19 period. By exploring whether banks' commitment to sustainability reporting and effective risk management practices contribute to their profitability, the study provides valuable insights for stakeholders, policymakers, and investors seeking to improve corporate performance. The research data are analyzed using descriptive statistics and panel regression with SPSS. Through purposive sampling, 70 banking companies were selected. The findings reveal that sustainability reporting does not significantly impact the profitability of Indonesian publicly listed banks. While risk management was measured with three proxies, with NPL having a significant impact, CAR and LDR showed mixed findings with significance and nonsignificance on profitability. Additionally, bank size and the COVID-19 period which serve as control variables significantly influenced the relationship between the independent and dependent variables.